Perceived neighbourhood affluence, mental health and wellbeing influence judgements of threat and trust on our streets: An urban walking study - Corcoran, Rhiannon (PLoS One, 2018)
This study aimed to understand how people respond to different urban neighbourhoods. We explored whether participants’ mental health and wellbeing, judgements of resident wealth, family SES and sentiments reflected in descriptions of place features predicted in situ sense of threat and trust. Forty-six student participants walked in groups through 2 urban neighbourhoods, separated by a park, in the North West of England, noting responses at pre-determined stops. Significant differences existed in participants’ sense of trust and threat between the 2 neighbourhoods along with differences in perceived resident wealth and sentiments expressed. Participants’ levels of persecutory ideas and their sense of residents’ wealth predicted in situ trust in both neighbourhoods while level of personal resilience predicted the extent of threat felt in the more deprived neighbourhood. Demonstrating the value of the method, these findings have implications for the governance of urban neighbourhoods whereby obvious cues signalling a harsh environment need to be minimised to create more positive psychological responses to places.